Law enforcement on plastic waste pollution in coastal area assessed from article 29 verse (4) law number 18 of 2008 concerning waste management (study in Buton regency of South Sulawesi) - La Gurusi (Jurnal Hukum Volkgeist, 2020)
This study focuses on the law enforcement process against plastic waste pollution in the Coastal Area of ​​Buton Regency and what factors impose law enforcement on plastic waste pollution in the Coastal Area of ​​Buton Regency. This study uses an empirical research model, namely legal research that analyzes and examines the work of law in society. The work of law in society can be examined through the effectiveness of law enforcement. Location of research on Law Enforcement Against Plastic Waste Pollution in Coastal Areas in View of Article 29 Paragraph (4) of Law Number 18 Year 2008 concerning Waste Management in Wasuemba Village, Pasarwajo District, Buton Regency, Southeast Sulawesi. To solve legal problems in this study, researchers used qualitative analysis. This study found that Enforceability of law is determined by (a) the availability of sanctions that can have a deterrent effect; (b) the availability of 3 (three) types of sanctions, consisting of administrative, criminal and civil sanctions; (c) availability of a public complaint mechanism and its follow-up on violations of rights experienced by the community; (d) availability of a regulatory oversight mechanism against environmental requirements; (e) the availability of special institutions and apparatuses to supervise compliance, investigate, investigate, prosecute, even court.